Landslide Susceptibility and Educational Facility Exposure in Majalengka Regency: A GIS-Based Weighted Overlay Approach - Muhammad Hafidz Aditya Ramadhan; Hermawan Setiawan; Andri Noor Ardiansyah (Department of Social Studies Education, Faculty of Tarbiyah and Teacher Training, Datokarama State Islamic University of Palu, Central Sulawesi, Indonesia., 2026)
Landslides are a significant geomorphological hazard in Indonesia that can damage infrastructure and disrupt social activities. In Majalengka Regency, variations in topographic conditions result in different levels of landslide susceptibility, which may affect public facilities, including educational institutions. This study aims to analyze the spatial distribution of landslide susceptibility and evaluate the exposure of educational facilities using a GIS-based Weighted Overlay method with seven parameters. The results indicate that High and Very High susceptibility areas cover approximately 33,284 hectares and 17,388 hectares, respectively, and are mainly concentrated in the southern part of Majalengka Regency. Of the 672 educational facilities, 162 schools (24.1%) are located within landslide-prone zones, including 47 schools in Very High susceptibility areas. These findings highlight the influence of terrain conditions, rainfall, soil characteristics, and proximity to infrastructure in shaping landslide susceptibility. This study provides a spatially explicit evaluation of educational facility exposure, offering empirical baseline data to support local disaster mitigation strategies and school safety planning.